Transistor, manufacturing method thereof and electronic device

By forming a conductive penetration part in the transistor to directly connect the electrode and the two-dimensional electronic gas, the problem of high contact resistance of the transistor during ohmic contact is solved, and the electrical performance of the device is improved.

CN119835986AActive Publication Date: 2025-04-15BEIJING ZHONGTENG NANO ENERGY TECHNOLOGY CO LTD +2

Patent Information

Application Number
CN202411976393.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-15
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The contact resistance of existing transistors during ohmic contact is high, which affects the device's working efficiency and output power.

Method used

By stacking the channel layer and the barrier layer in sequence on the substrate, and forming a titanium alloy layer and a gold layer on the barrier layer using coating technology, followed by heat treatment to form a conductive penetration part and an electrode, which directly connects to the two-dimensional electron gas in the electrode and channel layer through the barrier layer.

Benefits of technology

The direct contact between the electrode and two-dimensional electronic gas is achieved, reducing the contact resistance during ohmic contact, thereby improving the electrical performance of the transistor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119835986A_ABST
    Figure CN119835986A_ABST
Patent Text Reader

Abstract

The invention discloses a transistor, a manufacturing method thereof and an electronic device, manufacturing materials of an electrode comprise titanium alloy and gold alloy, a conductive penetrating part penetrates through a barrier layer and is directly connected with two-dimensional electron gas in the electrode and a channel layer, direct contact between the electrode and the two-dimensional electron gas is achieved, and the reliability of the transistor is improved. When the contact between the electrode and the two-dimensional electron gas is ohmic contact, the contact resistance during ohmic contact can be reduced due to the existence of the conductive penetrating part, so that the electrical property of the transistor is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of semiconductor technology, and in particular to a transistor, a manufacturing method thereof and an electronic device. Background Art

[0002] Compared with transistors with channels formed of silicon-based materials, transistors with channels formed of GaN materials show a larger bandgap, higher thermal conductivity and lower on-resistance, and can be used to prepare devices with lower energy loss and better reliability. The better the quality of the source / drain, the lower the contact resistance during ohmic contact, which makes the device's working efficiency and output power higher. Therefore, how to reduce the contact resistance during ohmic contact has become a technical problem that needs to be solved in this field. Summary of the invention

[0003] The embodiment of the present invention provides a transistor, a manufacturing method thereof and an electronic device, which are used to reduce the contact resistance during ohmic contact.

[0004] In a first aspect, an embodiment of the present invention provides a transistor, comprising: a substrate, and a channel layer and a barrier layer sequentially stacked on the substrate;

[0005] The transistor further includes: an electrode disposed on a side of the barrier layer away from the channel layer, the electrode including at least one of a source electrode and a drain electrode, and the material of the electrode including: a titanium alloy and a gold alloy;

[0006] The transistor further includes a conductive penetration portion, which passes through the barrier layer and is directly connected to the electrode and the two-dimensional electron gas in the channel layer respectively.

[0007] In a second aspect, an embodiment of the present invention provides a method for manufacturing a transistor, comprising:

[0008] A channel layer and a barrier layer are sequentially stacked on the substrate;

[0009] Using coating technology, a titanium alloy layer and a gold layer are sequentially stacked on the barrier layer;

[0010] The substrate on which the titanium alloy layer and the gold layer are formed is heat-treated to form a conductive penetration portion and an electrode. The conductive penetration portion passes through the barrier layer and is directly connected to the electrode and the two-dimensional electron gas in the channel layer respectively. The materials used to make the electrode include: a titanium alloy and a gold alloy formed by the titanium alloy in the titanium alloy layer and the gold in the gold layer.

[0011] In a third aspect, an embodiment of the present invention provides an electronic device, including: the above-mentioned transistor provided by an embodiment of the present invention.

[0012] The beneficial effects of the present invention are as follows:

[0013] A transistor, a manufacturing method thereof, and an electronic device provided by an embodiment of the present invention, wherein the manufacturing materials of the electrode include titanium alloy and gold alloy, the conductive penetration portion passes through the barrier layer, and is directly connected to the electrode and the two-dimensional electron gas in the channel layer, respectively, thereby realizing direct contact between the electrode and the two-dimensional electron gas. When the contact between the electrode and the two-dimensional electron gas is ohmic contact, the presence of the conductive penetration portion can reduce the contact resistance during ohmic contact, thereby improving the electrical performance of the transistor. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 A schematic diagram of the structure of a transistor provided in an embodiment of the present invention;

[0015] Figure 2 A flowchart of a method for manufacturing a transistor provided in an embodiment of the present invention;

[0016] Figure 3 A schematic diagram of the structure of an electronic device provided in an embodiment of the present invention;

[0017] Figure 4 The test result diagram of the contact resistance of Example 1 provided in the embodiments of the present invention;

[0018] Figure 5 A topographical diagram of the source electrode of Example 1 provided in an embodiment of the present invention;

[0019] Figure 6 Element distribution diagram of Example 1 provided in the embodiments of the present invention;

[0020] Figure 7 is an output curve of the transistor of Example 1 provided in an embodiment of the present invention;

[0021] Figure 8 This is a transfer characteristic curve of Example 2 provided in the embodiments of the present invention. DETAILED DESCRIPTION

[0022] The following will be combined with the accompanying drawings to describe in detail a transistor, a method for manufacturing the transistor, and a specific implementation of an electronic device provided by an embodiment of the present invention. It should be noted that the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] An embodiment of the present invention provides a transistor, such as Figure 1As shown, the transistor may include: a substrate 10, and a channel layer 20 and a barrier layer 30 stacked in sequence on the substrate 10; the transistor also includes: an electrode 40 arranged on the side of the barrier layer 30 away from the channel layer 20, the electrode 40 includes at least one of a source 41 and a drain 42, for example: when there is one electrode 40 arranged on the side of the barrier layer 30 away from the channel layer 20, the electrode 40 may be the source 41 or the drain 42, or when there are two electrodes 40 arranged on the side of the barrier layer 30 away from the channel layer 20, the two electrodes 40 may be the source 41 and the drain 42 respectively; the manufacturing material of the electrode 40 includes: titanium alloy and gold alloy; the transistor also includes a conductive penetration portion 50, the conductive penetration portion 50 passes through the barrier layer 30 and is directly connected to the electrode 40 and the two-dimensional electron gas 21 in the channel layer 20 respectively.

[0024] In this way, the conductive penetration portion 50 passes through the barrier layer 30 and is directly connected to the electrode 40 and the two-dimensional electron gas 21 in the channel layer 20 respectively, thereby achieving direct contact between the electrode 40 and the two-dimensional electron gas 21. When the contact between the electrode 40 and the two-dimensional electron gas 21 is ohmic contact, the contact resistance between the electrode 40 and the two-dimensional electron gas 21 can be reduced. For example, the contact resistance between the electrode 40 and the two-dimensional electron gas 21 can be no more than 0.15Ωmm, thereby improving the electrical performance of the transistor.

[0025] Optionally, the channel layer 20 may be made of, but not limited to, other materials such as GaN, and the barrier layer 30 may be made of, but not limited to, other materials such as AlGaN or AlN. The materials may be specifically configured according to actual needs. As long as the material can form a two-dimensional electron gas 21 on the side of the channel layer 20 facing the barrier layer 30, it falls within the protection scope of the embodiments of the present invention.

[0026] Optionally, the types of titanium alloy and gold alloy in the electrode 40 may include the following:

[0027] The first type: titanium alloy includes: at least one of titanium-magnesium alloy, titanium-tin alloy, titanium-magnesium-tantalum alloy, titanium-magnesium-vanadium alloy, titanium-tin-tantalum alloy, and titanium-tin-vanadium alloy.

[0028] At this time, the gold alloy can be an alloy formed by at least part of the elements in the titanium alloy except titanium and the gold element; for example but not limited to: the titanium alloy is a titanium-magnesium alloy, and the gold alloy is a gold-magnesium alloy; or, the titanium alloy is a titanium-tin alloy and a titanium-tin-vanadium alloy, and the gold alloy is a gold-tin-vanadium alloy, a gold-tin alloy, or a gold-tin alloy and a gold-tin-vanadium alloy, etc., which are not listed one by one here.

[0029] Among them, titanium will react with semiconductor materials in a solid phase to form defects and vacancies; magnesium and tin have low melting points and good fluidity. When defects and vacancies are formed, these elements can enter the barrier layer 30 along the defects and vacancies, destroy the lattice structure, and promote the formation of the conductive penetration part 50; tantalum and vanadium can provide a diffusion channel for the conductive penetration part 50 to grow toward the channel layer 20, so as to form a larger conductive penetration part 50. In this way, when these elements are selected to form titanium alloys and gold alloys, it is more conducive to forming a deeper and larger conductive penetration part 50, thereby reducing the contact resistance.

[0030] The second type: titanium alloy includes titanium aluminum alloy.

[0031] At this time, the gold alloy may be an alloy formed by at least part of the elements in the titanium alloy except titanium and the gold element; for example, the gold alloy is a gold-aluminum alloy.

[0032] Since aluminum has a low melting point and good fluidity, when defects and vacancies are formed, these elements can enter the barrier layer 30 along the defects and vacancies to destroy the lattice structure, thereby promoting the formation of the conductive penetration portion 50 .

[0033] It should be noted that in this second type, the role of titanium element is the same as that introduced in the first type, and will not be described in detail here.

[0034] The third type: based on the second type, the titanium alloy also includes at least one of titanium aluminum tantalum alloy and titanium aluminum vanadium alloy.

[0035] At this time, the gold alloy can be an alloy formed by at least part of the elements in the titanium alloy except titanium and the gold element; for example but not limited to: the gold alloy is at least one of a gold-aluminum alloy, a gold-aluminum-tantalum alloy, and a gold-aluminum-vanadium alloy.

[0036] It should be noted that in this third type, the role of tantalum and vanadium elements is the same as that of tantalum and vanadium elements introduced in the first type, and will not be described in detail here.

[0037] In summary, among titanium alloys and gold alloys, elements with suitable melting points, good fluidity and the ability to form alloys with titanium and gold can be selected, such as but not limited to: a heat treatment process is used when forming the conductive penetration portion 50, and the heat treatment temperature generally does not exceed the cracking temperature of the semiconductor layer manufacturing material. At this time, an element with a melting point not higher than the cracking temperature is selected so that the element can flow during the heat treatment, thereby growing the conductive penetration portion 50. In other words, metal elements or non-metal elements that can flow within the heat treatment temperature and can form alloys with titanium and gold can be used to form the electrode 40, and such elements are not limited to magnesium, tin, aluminum, tantalum and vanadium, but can also be other elements with similar properties.

[0038] Optionally, the thickness d0 of the electrode 40 can be set to 100nm to 400nm, such as but not limited to: 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 4000nm and other thicknesses, which are not listed here one by one and can be set according to actual needs.

[0039] Optionally, the conductive penetration portion 50 may be formed by connecting a plurality of penetration islands. Compared with the prior art in which each penetration island exists separately, the contact area between the electrode 40 and the two-dimensional electron gas 21 is increased, thereby further reducing the contact resistance.

[0040] Optionally, since the conductive penetration portion 50 is relatively close to the two-dimensional electron gas 21, when the conductive penetration portion 50 includes titanium nitride, the distance between the electrode 40 and the two-dimensional electron gas 21 is shortened, the potential barrier between the electrode 40 and the two-dimensional electron gas 21 can be reduced, and the electron tunneling effect is increased, thereby reducing the contact resistance.

[0041] Furthermore, the conductive penetration portion 50 includes a third alloy, which may be in a mesh structure and dispersed in the conductive penetration portion 50, which is beneficial to increase the lateral area of ​​the conductive penetration portion 50 and reduce the contact resistance. It should be understood that the lateral area of ​​the conductive penetration portion 50 refers to the area of ​​the cross section of the conductive penetration portion 50 parallel to the surface of the substrate 10.

[0042] Further, the third alloy may be an alloy formed by at least some elements other than titanium in the titanium alloy and the gold element; in other words, during the heat treatment process, when defects and vacancies are formed on the surface of the barrier layer 30, the gold alloy may enter the barrier layer 30 along the defects and vacancies, so that the volume of the gold alloy in the barrier layer 30 gradually increases and is dispersed in a network structure, and the third alloy may be the same as the gold alloy. Alternatively, the third alloy may be an alloy composed of elements that enter the barrier layer 30 along the defects and vacancies, in which case the third alloy may be different from the gold alloy.

[0043] Optionally, in addition to the above-described structure, the transistor may also include other structures for realizing transistor functions, for example, the transistor further includes a gate 43, the gate 43 may be located on the side of the barrier layer 30 away from the channel layer 20, and the gate 43 is located between the source 41 and the drain 42. Furthermore, the transistor may be a high electron mobility transistor, a field effect transistor or other types of transistors, as long as the transistor includes the two-dimensional electron gas 21, it belongs to the scope of the transistor to be protected by the embodiments of the present invention.

[0044] Based on the same inventive concept, an embodiment of the present invention provides a method for manufacturing a transistor, such as Figure 2 As shown, the manufacturing method is used to manufacture the transistor introduced in the above content, and the manufacturing method may include:

[0045] S201, sequentially stacking a channel layer and a barrier layer on a substrate;

[0046] S202, using a coating technology to sequentially stack a titanium alloy layer and a gold layer on the barrier layer;

[0047] S203, heat-treating the substrate on which the titanium alloy layer and the gold layer are formed to form a conductive penetration portion and an electrode, wherein the conductive penetration portion passes through the barrier layer and is directly connected to the electrode and the two-dimensional electron gas in the channel layer respectively; the electrode is made of materials including: a titanium alloy and a gold alloy formed by the titanium alloy in the titanium alloy layer and the gold in the gold layer.

[0048] Since ion implantation, regeneration or etching is usually used to form ohmic contact in the prior art, the embodiments of the present invention do not require ion implantation, regeneration or etching as in the prior art, and ohmic contact can be formed by using coating technology and heat treatment technology, and the formed conductive penetration portion can be directly connected to the electrode and the two-dimensional electron gas in the channel layer, respectively, thereby reducing the contact resistance between the electrode and the two-dimensional electron gas, thereby reducing the contact resistance during ohmic contact, and can also ensure the integrity of the heterojunction structure formed by the channel layer and the barrier layer, and of course, can also reduce the manufacturing cost.

[0049] Optionally, when forming the titanium alloy layer, the selected titanium alloy may include: at least one of titanium-aluminum alloy, titanium-aluminum-tantalum alloy, titanium-aluminum-vanadium alloy, titanium-magnesium alloy, titanium-magnesium-tantalum alloy, titanium-magnesium-vanadium alloy, titanium-tin alloy, titanium-tin-tantalum alloy, titanium-tin-vanadium alloy and other other alloys; these titanium alloys easily react with gold and elements in the semiconductor layer during heat treatment, thereby promoting the growth of the conductive penetration part, thereby enabling direct connection between the electrode and the two-dimensional electron gas and reducing the contact resistance.

[0050] It should be understood that the type of titanium alloy in the titanium alloy layer remains basically unchanged before and after heat treatment. In other words, if the titanium alloy in the titanium alloy layer is a titanium-magnesium alloy before heat treatment, then after heat treatment, the titanium alloy in the electrode is still a titanium-magnesium alloy, but the amount of titanium-magnesium alloy after heat treatment is less than the amount before heat treatment. In this reduced part of titanium-magnesium alloy, titanium is used to form titanium nitride in the conductive penetration part, and magnesium is used to form a gold alloy and a third alloy.

[0051] Of course, after the heat treatment, an alloy including titanium and gold may exist in the electrode or the conductive penetration portion, and this alloy can also be used to form the conductive penetration portion.

[0052] Among them, in the titanium alloy, the atomic percentage ratio of titanium to other elements can be set according to actual needs, such as but not limited to: 2:1, 1:1, 1:2, 1:3, 1:4, 9:11 and other ratios, which are not specifically limited here.

[0053] Furthermore, at least one titanium alloy layer may be provided. When a plurality of titanium alloy layers are provided, the materials used for two adjacent titanium alloy layers may be different, and the materials used for two non-adjacent titanium alloy layers may be the same or different, so that at least some of the titanium alloy layers in all the titanium alloy layers are made of different materials. This can meet the design requirements of different application scenarios, and can also realize a combination of multiple titanium alloys, utilizing the effects of different titanium alloys to further promote the growth of the conductive penetration portion.

[0054] The thickness of each titanium alloy layer can be set to 80nm to 120nm, such as but not limited to: 80nm, 85nm, 90nm, 95nm, 100nm, 110nm, 120nm and other thicknesses, which are not listed here one by one and can be set according to actual needs.

[0055] The thickness of the gold layer can be set to 50nm to 200nm, such as but not limited to: 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm and other thicknesses, which are not listed here one by one and can be set according to actual needs.

[0056] Optionally, when the titanium alloy layer and the gold layer are formed by the coating technology, other technologies such as magnetron sputtering technology may be used but are not limited to it; when performing heat treatment, rapid annealing may be used to make the electrode form an ohmic contact with the two-dimensional electron gas, the annealing temperature range may be set to, but are not limited to, 800°C to 950°C, the annealing time may be set to, but are not limited to, 30S to 90S, and the gas introduced during annealing is an inert gas, such as, but not limited to, nitrogen or argon. It should be understood that the parameters during annealing can be set according to actual needs and are not specifically limited here.

[0057] Based on the same inventive concept, an embodiment of the present invention provides an electronic device, such as Figure 3 As shown, the electronic device may include the above-mentioned transistor provided in the embodiment of the present invention, and of course may also include other active devices or passive devices, which may be specifically designed according to the function of the electronic device and are not limited here.

[0058] In summary, the above technical solution provided by the embodiment of the present invention has the following advantages:

[0059] 1. Currently, the widely used methods for realizing ohmic contact include: ion implantation, regeneration, and etching, but these methods will damage the heterojunction structure, thereby reducing the density of the two-dimensional electron gas and deteriorating the reliability of the device. The embodiment of the present invention adopts the coating technology + heat treatment technology to ensure the integrity of the heterojunction structure and avoid the reduction of the density of the two-dimensional electron gas, thereby improving the reliability of transistors and even electronic devices.

[0060] 2. The composition of the metal stack in the source and / or drain is optimized. After annealing, a conductive penetration portion is grown at the interface between the electrode and the semiconductor. The conductive penetration portion can be deep enough to directly contact the two-dimensional electron gas. The high conductivity of the components in the conductive penetration portion is used to achieve direct connection between the electrode and the two-dimensional electron gas, thereby obtaining a very low contact resistance.

[0061] The transistor is introduced below in conjunction with specific embodiments.

[0062] Embodiment 1: The channel layer is a GaN layer, the barrier layer is an AlGaN layer, the titanium alloy layer includes two film layers, which are titanium aluminum alloy layers and titanium aluminum tantalum alloy layers respectively, the source and drain both include a titanium alloy layer and a gold layer, and the material of the titanium alloy layer in the source and drain is the same.

[0063] The manufacturing process of the source and drain includes: using exposure technology to form a mask with a specific pattern on the AlGaN layer; using magnetron sputtering technology to deposit a titanium-aluminum alloy layer of a certain thickness on the mask, and the atomic percentage ratio of titanium and aluminum is 1:3; continuing to use magnetron sputtering technology to deposit a titanium-aluminum-tantalum alloy layer of a certain thickness on the titanium-aluminum alloy layer, and the atomic percentage ratio of titanium, aluminum and tantalum is 45:45:10; continuing to use magnetron sputtering technology to deposit a gold layer of a certain thickness on the titanium-aluminum-tantalum alloy layer; stripping off the mask so that the titanium-aluminum alloy layer, the titanium-aluminum-tantalum alloy layer and the gold layer at a specific position are retained, and the titanium-aluminum alloy layer, the titanium-aluminum-tantalum alloy layer and the gold layer at other positions are all stripped off; heat treating the stripped structure so that a conductive penetration portion grows in the AlGaN layer, thereby forming a source and a drain.

[0064] The manufacturing process of the channel layer, the barrier layer and the gate may adopt a manufacturing method well known to those skilled in the art, which will not be described in detail here.

[0065] See also Figure 4 As shown, Figure 4 (a) in FIG. 1 shows a fitting curve. By calculating the fitting curve, it is found that the contact resistance of the transistor is as low as 0.07Ωmm. Figure 4(b) in the figure shows the contact resistance of five randomly selected transistors. Among the five randomly selected transistors, the contact resistances are 0.07Ωmm, 0.08Ωmm, 0.10Ωmm, 0.11Ωmm and 0.15Ωmm respectively. The average value obtained by averaging these five values ​​is 0.10Ωmm, showing extremely low contact resistance.

[0066] See also Figure 5 As shown, Figure 5 (a) in the figure shows the surface morphology of the source in the embodiment. It can be found from the figure that the surface of the source is relatively flat, the structure is relatively refined, there are no large blocks, and there are no areas with uneven structure, which is conducive to improving the reliability of the transistor. Figure 5 (b) shows the cross-sectional morphology of the transistor. It can be seen from the figure that the edge of the source (such as Figure 5 The edge of the transistor (as indicated by the arrow in the figure) is sharp and neat, without any burr-like structures or discontinuous areas. This can avoid the deterioration of the breakdown performance of the transistor under high voltage due to the discontinuity of the edge, thereby helping to improve the voltage resistance and reliability of the transistor.

[0067] See also Figure 6 As shown, Figure 6 (a) shows a HAADF-STEM image of a transistor cross section, where the boundaries between the electrode, the conductive penetration portion, and the channel layer are clearly marked. It can be seen from the figure that the structure of the electrode is relatively uniform, and no large insoluble matter is found. This can avoid premature breakdown of the transistor under high electric fields due to large insoluble matter, which is beneficial to improving the voltage resistance of the transistor. In addition, an etched conductive penetration portion is found between the electrode and the channel layer. The conductive penetration portion has a large channel contact area and a flat profile. The flat, thornless surface profile can effectively prevent electric field concentration, thereby improving the voltage resistance and reliability of the transistor. Figure 6 (b) shows the distribution of Ti element near the interface. Figure 6 (c) shows the distribution of Al element near the interface. Figure 6 (d) shows the distribution of Ta element near the interface. Figure 6 (e) shows the distribution of Au elements near the interface. Figure 6 (f) shows the distribution of Ga element near the interface. Figure 6(g) in the figure shows the distribution of N element near the interface. Through the element distribution results, it is found that Ti and N elements are concentrated in the conductive penetration part, confirming that its composition is mainly TiN. Al, Au and Ta are concentrated in the conductive penetration part. Al-Au alloy can ablate Ga elements on the surface of the channel layer, expanding the growth path for the conductive penetration part, and the presence of Ta element provides a stable diffusion channel for Al-Au alloy to the semiconductor layer, which is conducive to the timely replenishment of Al-Au alloy. In this way, the conductive penetration part can continue to grow toward the semiconductor layer and obtain a greater growth depth and a smooth profile. Among them, the third alloy in the conductive penetration part is gold-aluminum-tantalum alloy.

[0068] See also Figure 7 As shown, Figure 7 (a) in the figure shows the output curve when the gate-source voltage is -10 to 6V, where the spacing between the source and the drain (i.e., the source-drain spacing) is 10μm, and the spacing between the gate and the drain (i.e., the gate-drain spacing) is 4μm; it can be found from the figure that at a gate-source voltage of 6V, the source-drain saturation current of the transistor is 792.15mA / mm, and the corresponding on-resistance is 5.45Ωmm, showing excellent output performance and extremely low conduction loss. Figure 7 (b) shows the breakdown characteristic curve, with a breakdown limit of 100μA / mm. It can be seen from the figure that when the gate-drain spacing is 4μm, 14μm, 24μm, and 29μm, the corresponding breakdown voltage is 632V, 707V, 865V, and 915V, respectively, showing excellent withstand voltage performance. The excellent output performance and extremely low conduction loss are attributed to the large contact area between the conductive penetration part and the two-dimensional electron gas, which improves the transmission efficiency of electrons, and the excellent withstand voltage performance is attributed to the flat surface morphology, uniform internal structure, and flat conductive penetration part profile, which effectively curb the electric field concentration and prevent the low-voltage breakdown of the transistor.

[0069] Embodiment 2: The differences from Embodiment 1 include: the titanium alloy layer includes two film layers, which are a titanium-aluminum alloy layer and a titanium-aluminum-vanadium alloy layer respectively, and the atomic percentage ratio of titanium, aluminum and vanadium in the titanium-aluminum-vanadium alloy layer is 45:45:10.

[0070] See also Figure 8As shown in the figure, the transfer characteristic curve is shown. During the test, the source-drain voltage is constant at 6V. It can be found from the figure that the threshold voltage of the transistor is about -8.89V. As the gate-source voltage increases, the two-dimensional electron gas channel gradually opens, and the transconductance gradually reaches the peak value. The magnitude of the transconductance reflects the opening ability of the channel. The larger the peak transconductance, the better the opening ability of the channel, and vice versa. The measured peak transconductance is 78.00mS / mm, indicating that the channel has good ability. In addition, as the gate-source voltage further increases, the current gradually approaches saturation. When the gate-source voltage reaches 6V, the source-drain current is 343.09mA / mm, showing good output performance.

[0071] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A transistor, characterized in that: include: A substrate, and a channel layer and a barrier layer sequentially stacked on the substrate; The transistor further comprises: an electrode disposed on a side of the barrier layer away from the channel layer, the electrode comprising at least one of a source electrode and a drain electrode, and the electrode is made of a material comprising a titanium alloy and a gold alloy; The transistor further includes a conductive penetration portion, which passes through the barrier layer and is directly connected to the electrode and the two-dimensional electron gas in the channel layer, respectively.

2. The transistor according to claim 1, characterized in that The titanium alloy includes at least one of titanium-magnesium alloy, titanium-tin alloy, titanium-magnesium-tantalum alloy, titanium-magnesium-vanadium alloy, titanium-tin-tantalum alloy and titanium-tin-vanadium alloy.

3. The transistor according to claim 1, wherein The titanium alloy includes titanium aluminum alloy, and the titanium alloy also includes at least one of titanium aluminum tantalum alloy and titanium aluminum vanadium alloy.

4. The transistor according to any one of claims 1 to 3, characterized in that: The gold alloy is an alloy formed by at least part of the elements in the titanium alloy except titanium and the gold element.

5. The transistor according to any one of claims 1 to 4, characterized in that: The contact resistance between the electrode and the two-dimensional electron gas is no more than 0.15Ωmm.

6. The transistor according to any one of claims 1 to 5, characterized in that: The conductive penetration portion includes titanium nitride therein.

7. The transistor according to any one of claims 1 to 6, characterized in that: The conductive penetration portion includes a third alloy, and the third alloy is in a mesh structure.

8. The transistor according to claim 7, characterized in that The third alloy is an alloy formed by at least part of the elements in the titanium alloy except titanium and gold.

9. A method for manufacturing a transistor, characterized in that: include: A channel layer and a barrier layer are sequentially stacked on the substrate; Using a coating technology, a titanium alloy layer and a gold layer are sequentially stacked on the barrier layer; Heat-treating the substrate on which the titanium alloy layer and the gold layer are formed to form a conductive penetration portion and an electrode, wherein the conductive penetration portion passes through the barrier layer and is directly connected to the electrode and the two-dimensional electron gas in the channel layer respectively; The electrode is made of materials including titanium alloy and gold alloy formed by the titanium alloy in the titanium alloy layer and the gold in the gold layer.

10. An electronic device, characterized in that: include: A transistor as claimed in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Semiconductor device

    JP2000174260A

  • Hetero-integrated strained silicon n-and p-MOSFETs

    US20060091377A1

Cited By

  • Transistor and manufacturing method therefor, and electronic device

    WO2026143915A1